Mapping the contours of organic agriculture : an exploratory study of an under-served population in South Africa - Du Plessis, Hendrik Pienaar (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.